Konstruksi Kandidat Gen AV1 Begomovirus pada pBI121 dan Introduksinya ke dalam Tembakau Menggunakan Vektor Agrobacterium tumefaciens - Tri Joko Santoso; Muhammad Herman; Sri H Hidayat; Hajrial Aswidinnoor; Sudarsono Sudarsono (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2011)
Construction of Begomovirus AV1 Gene Candidate intopBI121 and Its Introduction into Tobacco by usingAgrobacterium tumefaciens Vector. Tri J. Santoso,Muhammad Herman, Sri H. Hidayat, HajrialAswidinnoor, and Sudarsono. Infection of Begomovirushas caused leaf curl disease in tomato. This infection hassignificantly impact on yield losses of tomato production.Recently, in Indonesia there was no effectively way tocontrol this disease. The use of resistant tomato variety isone of strategies to control this virus. Genetic engineeringtechnology gives an opportunity to develop the transgenictomato resistant to Begomovirus through pathogen derivedresistance (PDR) approach. The objectives of this studywere to construct the Begomovirus AV1 candidate gene inthe pBI121 and to introduce the construct into tobacco plantgenome through Agrobacterium tumefaciens vector. A seriesactivites in gene construct have been conducted includePCR amplification of AV1 gene using a pair of specificprimer, cloning the gene into pGEM-T easy, transformation ofthe clone into Escherichia coli DH5α competent cell,construct the gene into pBI121, and transform the constructinto A. tumefaciens. Leaf segments of in vitro tobacco plantwere transformed by co-cultivation with A. tumefacienscontaining ToLCV-AV1 construct. In the research activitiy,Indonesian Begomovirus AV1 gene was successfullyamplified and inserted in expression vector plasmid pBI121.Tobacco transformants carrying kanamycin-resistant gene(nptII gene) were regenerated and established in theglasshouse. Those transformant plants are expectedcontaining the AV1 gene.